Performance-based Generative Shape Grammar Method: Energy Efficient Facade Design for Fully Glazed Multi-Storied Office Building - Hot and Humid Climate, Chennai, India - Chockalingam, Chandrasekaran; Sasidhar, Kumudhavalli; Anbu, Madhumathi (International Journal of Sustainable Construction Engineering and Technology, 2023)
The traditional building form design or form-making is an intuitive design method that is neither efficient nor competent for energy-efficient façade design. The form-making design approach threatens sustainable development in India. This paper discusses the new tread of form-finding, a process in which the framework is set for parameters to interact. It suggests a performance-based shape grammar (PBSG) generative design method for façade finding and evaluates it as an energy-efficient facade design method for FGM office buildings for India's hot and humid climate. A research method to develop PBSG rules for a given project framework was demonstrated by redesigning a case sample site and evaluating the existing FGM office building in the sample site. The PBSG methods in two stages apply multiple rules, first for form-finding and later for façade plane-finding for energy efficiency. It was observed that the SG resultant generated form was 42% more energy-efficient than the existing design using the same envelope materials, HVAC equipment, development regulations, and context. The outcome of this study provides a framework for a generative design process using PBSG in the early design stages and proves to be an energy-efficient design method for India's hot and humid climate.